2014
DOI: 10.3892/mmr.2014.2949
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Stat1-HDAC4 confers resistance to etoposide through enhanced multidrug resistance 1 expression in human A549 lung cancer cells

Abstract: Despite efforts to develop efficient chemotherapeutic drug strategies to treat cancer, acquired drug resistance is a commonly encountered problem. In the present study, to investigate this phenomenon, human A549 lung cancer cells resistant to the topoisomerase inhibitor etoposide (A549RT‑eto) were used and compared with A549 parental cells. A549RT‑eto cells demonstrated increased resistance to etoposide‑induced apoptosis when compared with A549 parental cells. Notably, A549RT‑eto cells were observed to exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 23 publications
4
27
0
Order By: Relevance
“…Chao et al (35) revealed that the mRNA expression of MRP in ovarian cancer cell was reduced after HDACs inhibitors treatments. Kaewpiboon et al (36) found that the level of PgP in human lung cancer cells resistant to etoposide was increased, and could be reversed by HDACs inhibitors. Therefore, in vitro studies have not demonstrated consistent results about the influence of HDAC inhibitor treatments on expression of tumor drug-resistance-related proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Chao et al (35) revealed that the mRNA expression of MRP in ovarian cancer cell was reduced after HDACs inhibitors treatments. Kaewpiboon et al (36) found that the level of PgP in human lung cancer cells resistant to etoposide was increased, and could be reversed by HDACs inhibitors. Therefore, in vitro studies have not demonstrated consistent results about the influence of HDAC inhibitor treatments on expression of tumor drug-resistance-related proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Gastric cancer progression can be enhanced by HDAC4 via p21 inhibition . STAT1/HDAC4 augmentation makes human A549 lung cells resistant to etoposide via increased MDR1 . High levels of HDAC4 are found and contribute to oncogenesis in liver cancer .…”
Section: Introductionmentioning
confidence: 99%
“…This has been shown as HDAC overexpression leads to more effective detoxification due to the HDAC2 and 4 dependent expression of the efflux pump p-glycoprotein. Consequently, colorectal and lung cancer cells resist doxorubicin and etoposide, respectively, which could be reversed upon HDACi application (17,49). HDACi furthermore influence detoxification by decreasing the levels of glutathione, thereby sensitising squamous cell carcinoma cells to cisplatin (50), a known target of detoxification by glutathione (51).…”
Section: Introductionmentioning
confidence: 99%